Trust and distrust on the web: User experiences and website characteristics. (April 2015) - Seckler, Mirjam; Heinz, Silvia; Forde, Seamus; Tuch, Alexandre N.; Opwis, Klaus
Highlights: We examine the content of trustful and distrustful user experience reports on the web. Distrust is mostly an effect of graphical and structural design issues of a website. Trust is based on social factors such as reviews or recommendations by friends. Abstract: The aim of this research is to study the content of trustful and distrustful user experiences on the web to identify website characteristics that enhance trust or cause distrust. We collected users' reports about critical incidents and quantitative questionnaire data by means of an online survey. Results from N  = 221 participants suggest that distrust is mostly an effect of graphical (e.g., complex layout) and structural (e.g., pop-ups) design issues of a website, whereas trust is based on social factors such as reviews or recommendations by friends. The content of a website affects both trust and distrust: privacy issues had an effect on distrust and security signs enhanced trust. Furthermore, we show how trustful and distrustful user experiences differ in terms of perceived honesty, competence, and benevolence. High honesty and competence characterize a trustful experience, whereas a distrustful experience is associated with missing honesty and missing benevolence. We discuss how different website characteristics help to enhance trust or to prevent distrust and how this impacts the allocation of design resources.